2019
DOI: 10.31580/jei.v6i4.1031
|View full text |Cite
|
Sign up to set email alerts
|

Supply Chain Sustainability Practices of Oil Servicing Firms in the Downstream Sector of Nigeria’s Oil and Gas Industry

Abstract: This study investigates the nature and context-based peculiarities of sustainability practices related to the supply chain of oil servicing firms operating in the downstream sector of Nigerian oil and gas industry. The supply chain management practices of oil servicing firms are crucial to the functioning of the downstream sector of the oil and gas industry. However, the literature on their supply chain sustainability is scant and scattered. To fully explore this field; therefore, survey data were collected fr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
0
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 21 publications
0
0
0
Order By: Relevance
“…SSCM practices are now a need for businesses that wish to flourish in the business sector. In order to improve organizational operations, boost the organization's profitability index, increase customer satisfaction, and contend with the pressure of competition present in the business environment, sustainable supply chain management is required (Abba, Norhayati & Salisu, 2019;Renato, Patricia, Otavio and Silvia, 2019). SSCM is a fundamental component in improving an organization's effectiveness and innovativeness since it has a favorable effect on the performance of the organization.…”
Section: Sustainable Supply Chain Management and Firm Innovative Perf...mentioning
confidence: 99%
See 2 more Smart Citations
“…SSCM practices are now a need for businesses that wish to flourish in the business sector. In order to improve organizational operations, boost the organization's profitability index, increase customer satisfaction, and contend with the pressure of competition present in the business environment, sustainable supply chain management is required (Abba, Norhayati & Salisu, 2019;Renato, Patricia, Otavio and Silvia, 2019). SSCM is a fundamental component in improving an organization's effectiveness and innovativeness since it has a favorable effect on the performance of the organization.…”
Section: Sustainable Supply Chain Management and Firm Innovative Perf...mentioning
confidence: 99%
“…Renato, Patricia, Otavio and Silvia, (2019) discovered in their research that SSCM activities like the environmental, social, and economic dimensions have a substantial impact on an organization's performance. According to Abba, Norhayati and Salisu (2019), an organization's market performance, financial performance, and innovative performance all increase when SSCM is used effectively. Similar to this, the empirical study by Bright and Stephen, (2021) showed that increasing the use of SSCM inside a company will boost its competitive advantage and improve organizational performance.…”
Section: Sustainable Supply Chain Management and Firm Innovative Perf...mentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, as highlighted by Adam et al (2019), sustainability practices in the supply chain can also be enhanced through data analytics. In the Nigerian textile industry, understanding the supply chain's intricacies and adopting sustainable practices can potentially lead to more efficient operations and marketing strategies emphasising the industry's sustainability.…”
Section: Assessment Of the Effects Of Data Analytics On Marketing App...mentioning
confidence: 99%
“…Further, they added that the SCR (supply chain resilience) lowered the intention to invest in oil and gas SMEs in Ghana. Adam et al (2019) found that SCMP (supply chain management practicing) firms play a vital role in the downstream oil sector of Nigeria. They indicated the strategic interventions in the SCPM in the smooth operation of the downstream oil and gas firms in Nigeria.…”
Section: Introductionmentioning
confidence: 99%